SISTEM FERTIGASI RAIN PIPE OTOMATIS PADA MAIN NURSERY KELAPA SAWIT (Elaeis guineensis Jacq) BERBASIS MIKROKONTROLER ARDUINO UNO - Anri Kurniawan; Tri Wahyu Saputra; Anugerah Ramadan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2020)
This research conducted to designed, implemented, and tested an automatic rain pipe fertigation system using temperature and soil moisture sensors. The system applied to three irrigation treatments, namely manual fertilization, semi-manual fertilization, and automatic fertigation. The automatic fertigation actuator setting point is at temperature of  ≥ 31 ° C and humidity of ≤ 60% to turn on the water pump and nutrient pump then the water pump will shut down when the temperature value of 25 °C and humidity of  ≥ 80%. The results showed a significant difference in the use of irrigation water based on variance test results with an error value of 5%. The use of water from automatic fertigation is 12.770 ml or 65.9% more efficient than manual irrigation with the same growth in plant height. The height of oil palm plants in the main nursery with automatic fertigation is higher on days 7 to 12. Automatic fertilization requires a fertilizer of 1.8 tons per ha, less than manual fertilization which reaches 3 tons per ha. Keywords: fertigation, microcontroller, oil palm, sensors, soil moisture